2007
DOI: 10.1109/tvcg.2007.70560
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Multimodal Volume Rendering for Preoperative Planning of Neurosurgical Interventions

Abstract: Surgical approaches tailored to an individual patient's anatomy and pathology have become standard in neurosurgery. Precise preoperative planning of these procedures, however, is necessary to achieve an optimal therapeutic effect. Therefore, multiple radiological imaging modalities are used prior to surgery to delineate the patient's anatomy, neurological function, and metabolic processes. Developing a three-dimensional perception of the surgical approach, however, is traditionally still done by mentally fusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 19 publications
0
81
0
7
Order By: Relevance
“…Skull stripping. We implemented the skull stripping algorithm as presented by Beyer et al [4]. Although a complete segmentation would provide better results, we want to avoid the necessary user interaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skull stripping. We implemented the skull stripping algorithm as presented by Beyer et al [4]. Although a complete segmentation would provide better results, we want to avoid the necessary user interaction.…”
Section: Methodsmentioning
confidence: 99%
“…Khlebnikov et al suggested a system to find optimal access paths by interpreting tumors as light sources and determining the cost-function based on light transport [15]. A visualization system for the pre-operative planning was provided by Beyer et al, who proposed a multi-volume renderer employing cut-away views to allow for visual access to the brain structures of interest [4]. Furthermore, they included a skull peeling algorithm, which we have also incorporated into our system.…”
Section: Related Workmentioning
confidence: 99%
“…As exemplified by Beyer et al, 181 who used GPU-based raycasting to display fused multimodal brain datasets in real time for preoperative planning of neurosurgical procedures, there is a trend toward using TF-based methods for anatomical feature enhancement, tissue separation, and obtaining complementary diagnostic information from different image modalities. In a GPU-based raycasting framework, Weber et al 182 segmented a volume into regions in the form of branches of a hierarchical contour tree, and created a unique TF for each of these regions.…”
Section: Applicationsmentioning
confidence: 99%
“…Furthermore, to render large out-of-core datasets, Moloney et al 206 presented a volume bricking-based sort-first algorithm to balance parallelized data loading and frame-to-frame coherence. The bricked volume technique was also used by Beyer et al 181 to display multimodal volume using GPU raycasting. Similarly, Ljung 185 presented a multiresolution scheme to render large out-of-core CT human cadaver volumes using GPU raycasting, in which techniques such as load-on-demand data management and TF-based data reduction were employed.…”
mentioning
confidence: 99%
“…However, deriving these visualizations of high quality is a challenging task and an issue of ongoing research. Numerous such multimodal brain visualizations exist (such as [2,3]) , but (to our knowledge) no illustrative approaches have been employed so far. However, they appear to be quite suitable for this task, since the goal of these methods is to mimic hand-drawn sketches (as, e.g., in anatomy atlases) and discern important from unimportant information by emphasizing major features and neglecting irrelevant details.…”
Section: Introductionmentioning
confidence: 99%